A high antioxidant level in edible plants is associated with genotoxic properties - Wan-Ibrahim, W.I.; Sidik, K.; Kuppusamy, U.R. (2010)
Aqueous extracts from 20 Malaysian edible plants were screened for total phenolic content (TPC), antioxidant activity and genotoxic effects on freshly isolated human lymphocytes. Ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assays were performed to determine the antioxidant activity of the extracts. Single-cell gel electrophoresis (SCGE) or comet assay was carried out to determine the level of DNA damage in human lymphocytes. Of the 20 plant aqueous extracts tested, two exerted more than 50 DNA strand breaks (severe damage), nine exerted 25-50 strand breaks (moderate damage) and nine exerted <25 strand breaks (mild damage). Strong positive correlations between the extent of DNA damage and FRAP level (r = 0.816), DNA damage and TPC (r = 0.830) and DNA damage and DPPH radical scavenging activities (r = 0.859) were observed. It is evident from this study that plants rich in antioxidants have greater genotoxic effect. (C) 2010 Elsevier Ltd. All rights reserved.